Etiology and differential diagnosis of binocular diplopia in comitant and incomitant strabismus - O. V. Proskurina; E. P. Tarutta; T. Z. Khvedelidze; S. G. Harutyunyan; N. A. Aklaeva; A. V. Apaev (Российский офтальмологический журнал, 2023)
The article discusses the main etiological factors in the development of binocular diplopia and differential diagnostic signs of diplopia induced by late acquired comitant and incomitant strabismus.Purpose: to identify the most common causes of binocular diplopia in adults, and to assess typical features of various etiologies of binocular diplopia.Material and methods. 168 patients with binocular diplopia aged 6.5 to 85 years received a complete ophthalmological examination, which included a qualitative evaluation and characterization of the nature of diplopia, and determination of eye mobility in eight directions of gaze which indicated the affected muscle. A numerical assessment of diplopia was done using a prismatic compensator.Results. In 66.7% of cases, diplopia was induced by comitant strabismus, predominantly (96.4%) the converging one. A comitant strabismus with a small angle was observed more frequently than one with a larger angle: 5° or less, in 50% of cases, and 10° or less in 25% of cases. In 64.3% of cases, the deviation angle did not conform with the value of the compensating prism, which turned out to be twice as high as the “calculated values”. In 79.5% of cases, diplopia induced by comitant strabismus developed before the age of 45. In 33.3% of cases, diplopia was induced by incomitant strabismus, with the deviation angle varying from 0 to 35°, different directions of eye deviation, and limitation of mobility. In 44.6% of cases, mobility restrictions could not be visually detected. The deflection angle conformed to the strength of the compensating prism. In 58.9% of cases, diplopia induced by incomitant strabismus developed at the age of 45 years and older.Conclusion. Diplopia frequently develops in young and middle-aged people. The most common cause of the development of diplopia is a late acquired comitant converging strabismus with a small angle (5° or less), which develops in parallel with myopia. A correct identification of strabismus nature (comitant vs. incomitant), which induces diplopia, contributes to optimally choosing a further tactics for diplopia elimination.